Since g(-x) is equal to g(x), the function is an EVEN FUNCTION.
<h3>Is the given function even, odd or neither?</h3>
Given the function in the question;
g(x) = (4 + x²)/(1 + x⁴)
To determine if the function is even, odd or neither, we find g(-x) by substituting -x for all occurrence of x in the function.
g(x) = (4 + x²)/(1 + x⁴)
g(-1) = (4 + (-x)²)/(1 + (-x)⁴)
Simplify
g(-x) = (4 + x²)/(1 + x⁴)
Hence,
g(-x) = g(x)
Since g(-x) is equal to g(x), the function is an EVEN FUNCTION.
Learn more about even functions here: brainly.com/question/23446734
#SPJ1
Answer:
a=3
b=3
Step-by-step explanation:
(2xy)^4
----------------
4xy
Expand the numerator
2^4 x^4 y^4
---------------------
4xy
Simplify
16 x^4 y^4
---------------------
4xy
We know that a^b / a^c = a^(b-c)
16/4 * x^(4-1) y^(4-1)
4 x^3 y^3
Answer:
1242.81
Step-by-step explanation:
Answer:
I think its 46, hope this helps!!!